2018
DOI: 10.1016/j.jmb.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Lysine Acetylation of Isocitrate Dehydrogenase in Escherichia coli

Abstract: The Escherichia coli isocitrate dehydrogenase (ICDH) is one of the tricarboxylic acid cycle enzymes, playing key roles in energy production and carbon flux regulation. E. coli ICDH was the first bacterial enzyme shown to be regulated by reversible phosphorylation. However, the effect of lysine acetylation on E. coli ICDH, which has no sequence similarity with its counterparts in eukaryotes, is still unclear. Based on previous studies of E. coli acetylome and ICDH crystal structures, eight lysine residues were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 84 publications
4
54
0
Order By: Relevance
“…Indeed, the wild-type CS overexpressed in BL21(DE3) cells had no detectable acetylation ( Fig. 1), consistent with our previous studies on MDH and ICD which also showed that wild-type MDH and ICD purified from BL21(DE3) cells had no detectable acetylation [14,15]. To facilitate the purification process and remove truncated proteins due to the usage of the UAG stop codon as the signal for AcK incorporation, we fused a His 6 -tag to the C terminus of the CS.…”
Section: Generating Site-specifically Acetylated Cs Variantssupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, the wild-type CS overexpressed in BL21(DE3) cells had no detectable acetylation ( Fig. 1), consistent with our previous studies on MDH and ICD which also showed that wild-type MDH and ICD purified from BL21(DE3) cells had no detectable acetylation [14,15]. To facilitate the purification process and remove truncated proteins due to the usage of the UAG stop codon as the signal for AcK incorporation, we fused a His 6 -tag to the C terminus of the CS.…”
Section: Generating Site-specifically Acetylated Cs Variantssupporting
confidence: 90%
“…Site‐directed mutagenesis of lysine to glutamine has been used commonly to study protein acetylation. However, our previous study showed that such method sometimes could draw opposite conclusions with those derived from the approach of direct incorporation of acetyllysine (AcK) . So in this study, we utilized an optimized system to produce purely acetylated CS variants at specific sites listed above by the genetic code expansion strategy individually .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two central-metabolic enzymes showing different patterns of acetylation during growth on glucose versus xylose, acetylation does not appear to have any regulatory role, indicating that this posttranslational modification does not always have a regulatory role. To date, only a few enzymes have been shown to be sensitive to lysine acetylation (4,(6)(7)(8), and the vast majority of acetylated lysines likely have no effect on protein function or activity. That being said, it is also clear that some enzymes are sensitive to acetylation and, in these regards, have coopted this promiscuous modification for regulatory roles.…”
Section: Resultsmentioning
confidence: 99%
“…Besides eukaryotes, more and more proteomic studies have shown that lysine acetylation is also widely distributed in prokaryotic cells, enriched in metabolic pathways and protein biosynthesis [ 54 ]. Recently, our group has applied the genetic code expansion in studying two metabolic enzymes, malate dehydrogenase (MDH) and isocitrate dehydrogenase (ICDH) of E. coli [ 55 , 56 ]. Interestingly, although both enzymes are in the tricarboxylic acid (TCA) cycle, the effects of lysine acetylation are completely different: acetylation of MDH increased the enzyme activity, while acetylation of ICDH decreased the enzyme activity.…”
Section: Lysine Acetylation and Its Analogs By Genetic Code Expansmentioning
confidence: 99%